Preparation method and application of graded lignin high-stability anion dispersed rosin size

The mixing method of preparing low molecular weight lignin L95 and rosin by graded lignin, the problems of high equipment cost and long production cycle in the prior art were solved, and anionic dispersed rosin glue with high stability and excellent glue-to-sizing performance were prepared, which is suitable for Papermaking industry.

CN119491427APending Publication Date: 2025-02-21TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411473807.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, when preparing dispersed rosin glue, the equipment costs are high, the production cycle is long, and gases and organic matters are prone to escape during the drying process, affecting the stability and performance of the product.

Method used

Low molecular weight lignin L95 is prepared by graded lignin, and it is fully mixed with rosin in anhydrous ethanol, and the anhydrous ethanol is recovered by magnetic stirring and rotary evaporation, and finally dried in an oven to prepare a high-stability anionic dispersed rosin gum.

Benefits of technology

The prepared lignin anionic dispersed rosin glue has high stability, superior glue sizing performance and good hydrophobicity. It is suitable for the papermaking industry and reduces equipment costs and production cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491427A_ABST
    Figure CN119491427A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of graded lignin high-stability anion dispersed rosin size, and the preparation method comprises the following steps: step 1, weighing a lignin raw material, mixing with an ethanol solution, and continuously stirring at room temperature; performing vacuum filtration to obtain a lignin solution dissolved in ethanol; carrying out rotary evaporation on the solution to recover ethanol, drying the residual solid, and grinding to obtain the low-molecular-weight lignin L95; and 2, fully mixing low-molecular-weight lignin L95 and rosin in absolute ethyl alcohol, magnetically stirring the solution, carrying out rotary evaporation to recover absolute ethyl alcohol, and drying residues in a drying oven to obtain the graded lignin high-stability anion dispersed rosin size. The lignin anion dispersed rosin size with high stability and high sizing performance is prepared, rosin in the sizing agent ensures good hydrophobicity of the sizing agent, the preparation process is efficient, reaction conditions are mild and controllable, and the lignin anion dispersed rosin size has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material and sizing agent preparation, and in particular to a preparation method and application of graded lignin high-stability anionic dispersed rosin glue. Background Art

[0002] Sizing agents can give paper or paperboard resistance to ink, emulsion, and water, while improving the smoothness and other comprehensive properties of paper. Rosin is the most important and ideal in-stock sizing agent in the papermaking process because it has good sizing effect and high compatibility with pulp fibers and other sizing agents. In addition, my country is the world's largest rosin production base and has unique advantages in resources. Therefore, the study of rosin sizing agents is in line with my country's national conditions and has become an important research and development direction for papermaking sizing agents. The functional groups of rosin are mainly conjugated unsaturated double bonds and carboxyl groups. In the rosin sizing process, the polar carboxyl groups react with the hydrophilic paper surface to align the non-polar unsaturated double bonds in a directional manner, forming a stable hydrophobic surface with reduced free energy, achieving a hydrophobic effect.

[0003] However, the incompatibility of rosin and water limits the dispersibility of rosin in water systems. In order to overcome this technical difficulty, the most commonly used method is to emulsify the rosin to make it a water-soluble emulsion. The most common rosin sizing agents at present are cationic dispersed rosin glue and anionic dispersed rosin glue. The preparation of dispersed rosin glue requires heating or the use of organic solvents to reduce the aggregation state between rosin molecules, and then an emulsifier is used to reduce the interfacial tension between rosin and water, thereby forming a stable rosin emulsion. Common methods include high temperature and high pressure method, solvent method and normal temperature phase inversion method.

[0004] However, the high temperature and high pressure method requires the equipment to be able to operate under high temperature and high pressure conditions. This special process condition places high demands on the manufacture of the equipment, requiring the equipment to be able to withstand high temperature and high pressure. Therefore, the equipment manufacturing cost of this method is relatively high. In addition, due to the large investment in equipment, some small and medium-sized enterprises with limited funds may face greater economic pressure to adopt this method for production. Therefore, although this method can prepare high-quality dispersed rosin glue, its high equipment cost and investment requirements limit its application in some fields.

[0005] The cost of raw materials used in the preparation of dispersed rosin glue by solvent method is relatively high, which increases the preparation cost and may limit its use in some cost-sensitive applications; the entire sol-gel process usually takes several days or weeks, which prolongs the production cycle of the product and is a challenge for market demands that require rapid response; during the drying process, due to the presence of a large number of micropores in the gel, many gases and organic matter may escape and cause the gel to shrink. This not only affects the final form and performance of the product, but may also affect the stability of the product. These shortcomings show that although the preparation of dispersed rosin glue by solvent method has certain advantages, such as uniform mixing at the molecular level and easy incorporation of trace elements, its cost, time and drying process issues also need to be considered in practical applications.

[0006] The normal temperature phase inversion method is difficult to achieve finer particle size, the product is difficult to stabilize, and the system is thermodynamically unstable. Specifically, in the normal temperature phase inversion method, if the solid rosin is crushed according to the conventional process and then dispersed into water by a colloid mill or a high-speed disperser, it is difficult to achieve a finer particle size, resulting in poor product stability. In addition, dispersed rosin glue is an emulsion of solid rosin particles uniformly dispersed in water at room temperature, forming a thermodynamically unstable system, which is also a significant disadvantage.

[0007] The use of anionic surfactants can change the surface properties of rosin particles, enhance the electrostatic repulsion between particles, and make the rosin particles evenly dispersed in water. This process can be carried out at room temperature without the help of toxic organic solvents, and is an environmentally friendly and effective method. Lignin contains both hydrophilic (carboxyl, hydroxyl and carbonyl) and lipophilic (benzene ring skeleton) groups, so its molecules have certain surface activity and can be used as surfactants. Although lignin molecules have certain surface activity, due to their wide molecular weight distribution, complex molecular structure, lack of regular lipophilic and hydrophilic groups, it is difficult to arrange regularly at the interface of the two phases, and the surface activity is limited. Therefore, it is crucial to reduce the polydispersity of lignin and separate low molecular weight lignin by green and efficient methods. The main classification methods currently include membrane filtration classification, gradient precipitation classification, organic solvent dissolution classification, etc. Summary of the invention

[0008] In view of this, the present invention provides a preparation method and application of graded lignin high-stability anionic dispersed rosin glue.

[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0010] The preparation method of graded lignin high-stability anionic dispersed rosin glue comprises the following steps:

[0011] Step 1: Low molecular weight lignin L 95 Preparation

[0012] Weigh the lignin raw material, mix it with the ethanol solution, and continue stirring at room temperature; obtain a lignin solution dissolved in ethanol by vacuum filtration; then use rotary evaporation to recover ethanol from the solution, dry the remaining solid and grind it to finally obtain low molecular weight lignin L 95 ;

[0013] Step 2: Preparation of lignin anionic dispersed rosin glue LARS

[0014] Low molecular weight lignin L 95 and rosin in anhydrous ethanol and fully mixed, then the above solution is magnetically stirred, after completion, the anhydrous ethanol is recovered by rotary evaporation, and the residue is placed in an oven to dry, so as to obtain graded lignin high-stability anionic dispersed rosin glue.

[0015] Preferably, in step 1, the mass ratio of rosin to lignin is 1:2.

[0016] Preferably, in step 1, the volume concentration of the ethanol solution is 95%.

[0017] Preferably, in step 1, the stirring speed is 400 rpm and the stirring time is 2 h.

[0018] Preferably, in step 1, the drying temperature is 50°C.

[0019] Preferably, in step 2, the magnetic stirring time is 3 hours.

[0020] Preferably, in step 2, the drying temperature is 50°C and the drying time is 12 hours.

[0021] The application of the preparation method of graded lignin high-stability anionic dispersed rosin glue in the preparation of sizing agents.

[0022] Compared with the prior art, the present invention has achieved the following technical effects:

[0023] (1) The present invention prepares a lignin anionic dispersed rosin glue (LARS) with high stability and high sizing performance. 95 As a surfactant in the sizing agent system, it gives the sizing agent higher stability and also has excellent sizing performance; the rosin in the sizing agent ensures good hydrophobicity of the sizing agent. 95When the ratio of LARS to LARS is 1:2, the LARS sizing agent exhibits a minimum particle size of 270.00 nm, a maximum colloidal stability Zeta potential of -48.84 mV, a lower surface tension of 35.40 mN / m and an interfacial tension of 2.55 mN / m. The LARS sizing agent exhibits high storage stability and good sizing performance. The preparation process of the present invention is efficient, the reaction conditions are mild and controllable, and it has broad application prospects;

[0024] (2) In the present invention, lignin is first separated into a lignin fraction L having a smaller molecular weight by passing it through a 95% ethanol / water solution. 95 , improving the heterogeneity of lignin chemical structure and molecular weight. 95 It has strong lyophilicity and negative charge, and can evenly disperse rosin particles in water through electrostatic repulsion, thereby preparing lignin anionic dispersed rosin glue (LARS) with a stable dispersion state;

[0025] (3) The anionic lignin dispersed rosin glue with excellent sizing performance prepared by the present invention further expands the application scope of lignin. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and its application in different L 95 XPS spectrum of added amount of LARS sizing agent;

[0027] Figure 2 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 Optical microscope analysis of the added amount of LARS sizing agent;

[0028] Figure 3 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 Particle size (a) and PD I (b) of LARS sizing agent with added amount;

[0029] Figure 4 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 Zeta potential diagram of LARS sizing agent with added amount;

[0030] Figure 5 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 Surface tension diagram of LARS sizing agent with added amount;

[0031] Figure 6The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 Interfacial tension diagram of LARS sizing agent with added amount;

[0032] Figure 7 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 Creaming index diagram of added amount of LARS sizing agent at different times;

[0033] Figure 8 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 Sizing performance diagram of LARS sizing agent with added amount;

[0034] Wherein, (a) is the Cobb value; (b) is the edge penetration value; (c) is the contact angle;

[0035] Fig. 9 The invention discloses a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and different L 95 LARS sizing agent retention rate (a) and filtrate turbidity (b) of added amount;

[0036] Fig.10 The invention relates to a method for preparing a high-stability anionic dispersed rosin glue of graded lignin and its application. 95 Schematic diagram of a mechanism of action. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The invention discloses a method for preparing a graded lignin high-stability anionic dispersed rosin glue, comprising the following steps:

[0039] Step 1: Low molecular weight lignin L 95 Preparation

[0040] The lignin raw material was weighed, mixed with an ethanol solution with a volume concentration of 95%, and stirred at a speed of 400 rpm at room temperature for 2 hours; a lignin solution dissolved in ethanol was obtained by vacuum filtration, and the mass ratio of rosin to lignin was 1:2; the solution was then rotary evaporated to recover ethanol, and the remaining solid was dried at 50°C and then ground to finally obtain low molecular weight lignin L 95 ;

[0041] Step 2: Preparation of lignin anionic dispersed rosin glue LARS

[0042] Low molecular weight lignin L 95 and rosin in anhydrous ethanol and fully mixed, then the above solution was magnetically stirred for 3 hours, and then the anhydrous ethanol was recovered by rotary evaporation, and the residue was placed in a 50°C oven and dried for 12 hours to obtain graded lignin high-stability anionic dispersed rosin glue.

[0043] The application of the preparation method of graded lignin high-stability anionic dispersed rosin glue in the preparation of sizing agents.

[0044] Embodiment 1:

[0045] The experimental instruments and equipment are shown in Table 1.

[0046] Table 1 Experimental instruments and equipment

[0047] Instrument / Equipment Name Specifications / Models Manufacturer Electronic analytical balance AL204 Mettler Toledo Instruments (Shanghai) Co., Ltd. Digital cantilever agitator RW20Digital Aika (Guangzhou) Instrument Equipment Co., Ltd. Constant temperature magnetic stirrer B11-3 Shanghai Silo Instrument Co., Ltd. Electric blast dryer BAO-150A Shanghai Shidukai Instrument Equipment Co., Ltd. Ultrasonic Cleaner SB-5200DTD Ningbo Xinzhi Biotechnology Co., Ltd. Dynamic Light Scattering 90Plus / BI-MAS Brookhaven Instruments UV-Vis Spectrophotometer TU-1810 Beijing Puxi General Instrument Co., Ltd. Scanning electron microscopy (SEM) JSM-IT300LV Nippon Electronics Optical Microscope Ci-L Nikon Corporation White water circulation film copying machine S958540015 Germany FRANK-PTI Company Meter / Interfacial Tensiometer DCAT21 Dataphysics Dynamic contact angle tester PGX Swedish company FIBRO Automatic Cobb value tester 61-67 TMI Corporation

[0048] Experimental raw materials and drugs:

[0049] The raw materials used in this experiment were concentrated wastewater from wheat straw bio-mechanical pulping, bleached coniferous wood pulp, bleached hardwood pulp and high-yield pulp, all from Zhejiang Jingxing Paper Co., Ltd., China. The chemicals used are shown in Table 2.

[0050] Table 2 Experimental drugs

[0051]

[0052]

[0053] Experimental methods:

[0054] Step 1: Low molecular weight lignin (L 95 )

[0055] The lignin raw material was weighed and mixed with an ethanol solution having a volume concentration of 95%, and stirred at 400 rpm for 2 hours at room temperature. Subsequently, a lignin solution dissolved in ethanol was obtained by vacuum filtration. The solution was then rotary evaporated to recover ethanol, and the remaining solid was dried at 50°C and then ground to finally obtain low molecular weight lignin L 95 .

[0056] Step 2: Preparation of lignin anionic dispersed rosin size (LARS)

[0057] L 95and rosin were placed in 20 mL of anhydrous ethanol and mixed thoroughly (the mass ratio of rosin to lignin was 1:0.25, 1:0.5, 1:1, 1:2, 1:3 and 1:4), and then the above solution was stirred magnetically for 3 hours, and then the anhydrous ethanol was recovered by rotary evaporation, and the residue was placed in a 50°C oven and dried for 12 hours. 1 g of the above product was dissolved in 10 g of deionized water and ultrasonically dispersed for 30 minutes to obtain a LARS dispersion with a concentration of 10%.

[0058] X-ray Electron Spectroscopy (XPS) Detection:

[0059] The surface chemical analysis of the samples was performed using an X-ray photoelectron spectrometer. Test conditions: vacuum degree of 5×10-7mbar, fixed transmission energy of the energy analyzer of 50eV, surface sampling depth of 5.0-7.0nm, scanning width of 1000eV, and spectrum width of 1.00eV.

[0060] Optical microscope inspection:

[0061] Use a dropper to drop a proper amount of sizing agent on the slide, cover it with a coverslip, and place it on the stage for testing.

[0062] Particle size and zeta potential detection:

[0063] The particle size and Zeta potential of the lignin anion dispersed rosin glue were detected by dynamic light scattering. The sample mass concentration used in the detection was 0.1%, and the average value of three measurements was taken for analysis. The pH was not adjusted during the Zeta potential measurement.

[0064] Surface tension testing:

[0065] The static surface tension of the sizing agent was measured by the hanging plate method in a constant temperature water bath at 25°C using a surface / interface tension meter. Each sample was measured three times and the average value was taken.

[0066] Interfacial tension detection:

[0067] The interfacial tension of the sizing agent under different rosin and lignin ratios was monitored using an interfacial tension meter. 95 ) and oil phase (rosin) are placed in a syringe and a cuvette respectively. Each sample forms a 10 μL droplet at the tip of the syringe, and then the droplet is immersed in the cuvette. The computer calculates the interfacial tension value based on the Young-Laplace equation and the change in droplet area.

[0068] Lactation index test:

[0069] Take 5mL of sizing agent and put it into a test tube and record its height. Then place it on a horizontal table and store it at room temperature. Record the height change of the sizing agent clear liquid layer during different storage cycles. Calculate the creaming index (CI) using formula 4-1:

[0070]

[0071] Among them, Hs is the height of the clear liquid layer, and Ht is the total height of the sizing agent.

[0072] Condensation test:

[0073] The particle size of the freshly prepared sizing agent was measured by dynamic light scattering. After storage at room temperature for 48 hours, the particle size of the sizing agent was measured repeatedly. The coagulation degree was calculated using formula 4-2:

[0074] Coagulation degree = (A 48 -S 0 ) / S0×100% Formula (4-2)

[0075] Among them, S 0 is the particle size of the freshly prepared sizing agent, S 48 It is the particle size of the sizing agent after being placed for 48 hours.

[0076] Ultraviolet spectrum (UV-vis) determination:

[0077] The retention rate of the sizing agent in the paper sheet is determined by ultraviolet spectrophotometer. The specific method is as follows: prepare sizing agent solutions of 2mg / L, 5mg / L, 8mg / L, 10mg / L, 12mg / L, 15mg / L and 20mg / L respectively, use ultraviolet spectrophotometer to detect the absorbance value of its characteristic absorption peak at 280nm, and draw the standard curve corresponding to the sizing agent. Take a certain amount of papermaking white water, detect its absorbance value at 280nm, substitute it into the formula, and calculate the retention rate of the sizing agent in the paper sheet.

[0078] Filtrate turbidity determination:

[0079] Filter each slurry sample with medium-speed qualitative filter paper, place the filtered filtrate in the measurement chamber of the turbidity meter, and record the measurement results. Repeat the measurement 3 times for each sample and take the average value.

[0080] Sizing agent sizing performance test:

[0081] The contact angle was measured using a PGX dynamic contact angle tester according to standard ISO / TS14778:2021. The Cobb value was measured using a 61-67 automatic Cobb value tester according to standard GB / T 1540-2002. The edge penetration value was tested according to standard GB / T 31905-2015. The different conditions of the edge penetration test were: 95℃ deionized water for 10min; 75℃ 30% hydrogen peroxide solution for 10min; 21±1℃ 1% lactic acid solution for 1h.

[0082] The edge penetration value is calculated according to formula 4-3:

[0083]

[0084] Among them, G 1 is the mass of the paper sample at room temperature (g), G 2 is the mass of the paper sample at room temperature after soaking in different liquids (g), S is the circumference of the paper sample (mm), and D is the average thickness of the paper sample (μm).

[0085] LARS Sizing Agent XPS:

[0086] XPS spectroscopy was used to characterize the changes in the surface functional groups of LARS sizing agent particles. Figure 1 As shown in the figure, the C element signal of the sizing agent was analyzed and two peaks were found in the rosin, which were respectively attributed to CC (284.8 eV) and OC=O (288.5 eV). 95 In the LARS sizing agent system, three peaks appear, which are attributed to CC (284.8eV), OC=O (288.5eV) and COC (286eV). 95 The increase of the proportion of L in the sizing system 95 The proportion of ether bonds (COC) in the LARS sizing agent system is also gradually increasing. This result shows that the LARS sizing agent has been prepared. 95 As a dispersant covering the surface of rosin particles, it can ensure the stable dispersion of the sizing agent in water.

[0087] Microscopic morphology of LARS sizing agent:

[0088] like Figure 2 As shown, the morphology of the sizing agent droplets was observed by optical microscopy. 95 The presence of increases the effective contact area of ​​the oil-water interface and promotes the formation of emulsion droplets. 95 The different ratios of rosin and L lead to significant differences in the size distribution of the droplets. 95 When the added mass ratio is 1:2, the size and distribution of the sizing agent droplets are most uniform.

[0089] At the same time, it can be seen that rosin and L 95 When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0090] LARS sizing agent particle size:

[0091] L 95 Effects of sizing agent particle size Figure 3 As shown, when L 95 When the addition amount is low, the sizing agent particles increase with L 95 becomes smaller due to the addition of 95 The electrostatic repulsion between rosin particles is enhanced, making the rosin particles evenly dispersed in the aqueous solution. 95 When the addition ratio is greater than 1:2, the sizing agent particles become larger, which may be due to excessive L 95 The existence of destroys the balance of the system, and L 95 The sizing agent particle size increases. 95 When the ratio is 1:2, the particle size of the sizing agent is the smallest (270.00nm).

[0092] At the same time, it can be seen that rosin and L 95 When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0093] LARS sizing agent Zeta potential:

[0094] L 95 Effects on Zeta potential of sizing agents Figure 4 As shown, L 95 The addition of L affects the charge distribution state around the rosin particles in the sizing agent emulsion, resulting in a change in potential. 95 As the ratio increases, the absolute value of the sizing agent potential increases first and then decreases. 95 When the addition ratio of L is 1:2, the surface charge of the sizing agent is -48.84 mV, indicating that there is a strong electrostatic repulsion between the sizing agent droplets, making it difficult for the sizing agent droplets to aggregate, thereby improving the stability of the sizing agent emulsion. 95 When the addition amount is further increased, the rosin particles and L 95 The electrostatic equilibrium state between them causes the absolute value of the sizing agent's potential to decrease.

[0095] At the same time, it can be seen that rosin and L 95When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0096] LARS sizing agent table / interfacial tension:

[0097] Surface tension is the mutual attraction between liquid and gas (usually air) in the surface layer. Surface tension is caused by the strong cohesive force between liquid molecules. Interfacial tension is the tension between any two substances. Air-water surface tension and oil-water interfacial tension play an important role in determining the microstructure and stability of sizing agent emulsion. 95 The directional arrangement at the oil-water interface reduces the interfacial tension and increases the emulsion stability. 95 The effectiveness as a dispersant was analyzed by surface tension and interfacial tension.

[0098] LARS sizing agent surface tension:

[0099] like Figure 5 As shown, with L 95 As the ratio increases, the surface tension of the sizing agent shows two stages: first decreasing and then reaching equilibrium. This is because L 95 As the ratio increases, more and more L 95 Migrate and adsorb on the air-liquid interface, causing the surface tension of the sizing agent to drop rapidly; when L 95 The adsorption at the interface reaches saturation (rosin: L 95 The ratio of rosin and L 95 The micelles formed by aggregation reach the critical micelle concentration, the cohesive force decreases, and the surface tension no longer changes. At this time, the corresponding surface tension is 35.40 mN / m.

[0100] At the same time, it can be seen that rosin and L 95 When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0101] LARS sizing agent interfacial tension:

[0102] Table 3 Different L 95 Interfacial tension of added LARS sizing agent

[0103]

[0104] As shown in Table 3 and Figure 6 As shown, with rosin:L 95When the ratio of L increases from 1:0.25 to 1:3, the interfacial tension of the sizing agent decreases significantly; when the ratio increases to 1:4, the interfacial tension value of the sizing agent becomes unstable. This indicates that the appropriate amount of L 95 It can interact with rosin to change the adsorption capacity of rosin particles at the oil-water interface. This is because L 95 The two ends of the rosin particles and water are adsorbed and arranged in a certain way. 95 As a medium, it reduces the oil-water interfacial tension and makes the rosin particles evenly dispersed in the aqueous solution. 95 It will flocculate itself, resulting in instability of the numerical value when measuring the interfacial tension.

[0105] LARS sizing agent stability:

[0106] The sizing agent emulsion is a thermodynamically unstable system and is affected by many factors during long-term storage, such as emulsion particle size, coagulation state, and interaction forces between emulsions. It will eventually lose stability and experience emulsion precipitation, coagulation, and even phase separation.

[0107] LARS sizing agent emulsion index:

[0108] During the storage of the sizing agent, if the movement between the sizing agent particles through various interactions exceeds the Brownian motion, it will cause the sizing agent system to produce a concentration gradient, precipitation or phase separation, which can be represented by the creaming index. Figure 7 The different L 95 Effect of addition amount on the emulsion index of sizing agent.

[0109] When L 95 The ratio is too low (rosin: L 95 The ratio is 1:0.25) or too high (rosin:L 95 The ratio is 1:3; rosin: L 95 When the ratio of rosin:L is 1:4), the emulsion is almost unstable (CI>60% on the 365th day). 95 When the ratio is 1:2, the 365-day CI is 8%, indicating that the sizing agent has the best stability under this ratio. Figure 7 As far as we know, L 95 The presence of L can improve the stability of the emulsion, but too low or excessive L 95 will reduce the stability of the sizing agent emulsion. This may be because the appropriate amount of L 95 It can form a stable network structure between the sizing agent particles, preventing the sizing agent system from continuing to stratify, thereby improving the stability of the emulsion.

[0110] At the same time, it can be seen that rosin and L 95When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0111] LARS sizing agent coagulation degree:

[0112] Table 4 Different L 95 Added amount of LARS sizing agent coagulation degree

[0113]

[0114] Coagulation refers to the fusion of two or more emulsion droplets into a larger oil droplet, which may eventually lead to phase separation. Table 4 shows the different L 95 Effect of addition amount on coagulation degree of sizing agent. When the ratio of rosin:L95 is 1:0.25 and 1:4, the sizing agent emulsion shows obvious coagulation during storage. 95 When the ratio is 1:0.25, the coagulation degree of the emulsion is 4.72%, indicating that at this time L 95 The addition of can prevent the droplets from agglomerating and improve the stability of the sizing agent emulsion. The same conclusion as the above emulsion index, L 95 The presence of can improve the stability of the emulsion, but rosin and L 95 The ratio should be maintained at about 1:2. Too low or excessive L 95 All of them will reduce the stability of the sizing agent emulsion.

[0115] At the same time, it can be seen that rosin and L 95 When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0116] LARS sizing agent sizing performance:

[0117] Cobb value, contact angle and edge penetration value are usually used to evaluate the sizing performance of sizing agents. Cobb value is used to characterize the resistance of LPB core layer surface to liquid penetration. Figure 8 It can be seen that under the same sizing amount, rosin: L 95 When the ratio is 1:2, the sizing agent shows the best surface hydrophobicity (120s Cobb value = 6.2g / ㎡, 1200s Cobb value = 16.9g / ㎡). In addition, three different liquids were selected, namely 75℃ hydrogen peroxide solution (highly oxidizing liquid), 95℃ hot water (high temperature liquid) and 21℃ lactic acid (acidic liquid) to test the sizing performance of the sizing agent. The results are as follows Figure 8 b. When rosin: L 95When the ratio is 1:2, the edge penetration value of LARS sizing agent hydrogen peroxide solution at 75℃ is 0.54kg / ㎡; the edge penetration value of hot water at 95℃ is 0.67kg / ㎡; the edge penetration value of lactic acid at 21℃ is 0.75kg / ㎡.

[0118] LARS sizing agent hydrophobic properties:

[0119] LARS sizing agent still has the best edge hydrophobicity. In addition, at this ratio, the contact angle of the paper sheet is 142.2°. This means that the sizing agent has good sizing performance such as Figure 8 As shown in c.

[0120] At the same time, it can be seen that rosin and L 95 When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0121] LARS sizing agent retention performance:

[0122] Depend on Fig. 9 a It can be seen that when rosin: L 95 When the ratio of 1:2 is 1:2, the retention rate of the sizing agent is the highest (94.41%), which shows that the sizing agent prepared at this ratio can be well retained on the fiber. Fig. 9 b It can be seen that when rosin: L 95 When the ratio is 1:2, the turbidity of papermaking white water is the lowest, which is 4.57NTU, indicating that most of the sizing agent is retained in the fiber. The retention rate of the sizing agent is the highest at this ratio, which is consistent with the conclusion of the retention rate.

[0123] At the same time, it can be seen that rosin and L 95 When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0124] L 95 Mechanism of action:

[0125] like Fig.10 As shown, the main components of the sizing agent are rosin and L 95 Rosin is a hydrophobic substance. Due to its thermodynamic instability in the water phase, rosin particles tend to agglomerate. 95 When it exists as a dispersant in the two phases of rosin particles and water, the surface of the rosin particles is hydrophobic due to the hydrophobic effect, making the surface of the rosin particles 95 The hydrophobic group binding, L 95 The hydrophilic group (hydroxyl group) of L 95 The two ends of the rosin particles and water are adsorbed and arranged in a certain way, with L 95As a medium, a three-dimensional hydration film is formed on the surface of the rosin particles. When the rosin particles with three-dimensional hydration film approach each other, a strong repulsive force (spatial isolation steric hindrance or electrostatic steric hindrance) is generated, which can mechanically prevent aggregation and enable the rosin particles to disperse.

[0126] At the same time, it can be seen that rosin and L 95 When the added mass ratio is 1:2, the two have a synergistic effect and can synergistically improve the relevant properties of the prepared graded lignin high-stability anionic dispersed rosin glue.

[0127] The present invention prepares a lignin anionic dispersed rosin size (LARS) with high stability and high sizing performance. 95 As a surfactant in the sizing agent system, it gives the sizing agent higher stability and also has superior sizing performance; the rosin in the sizing agent ensures good hydrophobicity of the sizing agent. When the mass ratio of rosin: L95 is 1:2, the LARS sizing agent exhibits the lowest particle size (270.00nm), the highest colloidal stability (Zeta potential = -48.84mV), lower surface tension (35.40mN / m) and interfacial tension (2.55mN / m). The LARS sizing agent exhibits high storage stability (365-day CI = 8.00%; coagulation degree = 4.72%) and good sizing performance (120s Cobb value = 6.2g / ㎡, the edge permeability of hydrogen peroxide solution is 0.54kg / ㎡, the edge permeability of hot water is 0.67kg / ㎡, and the edge permeability of lactic acid is 0.75kg / ㎡). The preparation process of the present invention is efficient, the reaction conditions are mild and controllable, and it has broad application prospects.

[0128] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-stability anionic dispersed rosin glue of fractionated lignin, characterized in that: The steps include: Step 1: Low molecular weight lignin L 95 Preparation Weigh the lignin raw material, mix it with the ethanol solution, and continue stirring at room temperature; By vacuum filtration, a lignin solution dissolved in ethanol is obtained; the solution is then subjected to rotary evaporation to recover the ethanol, and the remaining solid is dried and ground to finally obtain low molecular weight lignin L 95 ; Step 2: Preparation of lignin anionic dispersed rosin glue LARS Low molecular weight lignin L 95 and rosin in anhydrous ethanol and fully mixed, then the above solution is magnetically stirred, after completion, the anhydrous ethanol is recovered by rotary evaporation, and the residue is placed in an oven to dry, so as to obtain graded lignin high-stability anionic dispersed rosin glue.

2. The method for preparing the fractionated lignin high stability anionic dispersed rosin glue according to claim 1, characterized in that: In the step 1, the mass ratio of rosin to lignin is 1:

2.

3. The method for preparing the fractionated lignin high stability anionic dispersed rosin glue according to claim 1, characterized in that: In step 1, the volume concentration of the ethanol solution is 95%.

4. The method for preparing the fractionated lignin high stability anionic dispersed rosin glue according to claim 1, characterized in that: In the step 1, the stirring speed is 400 rpm and the stirring time is 2 h.

5. The method for preparing the fractionated lignin high stability anionic dispersed rosin glue according to claim 1, characterized in that: In step 1, the drying temperature is 50°C.

6. The method for preparing the fractionated lignin high stability anionic dispersed rosin glue according to claim 1, characterized in that: In step 2, the magnetic stirring time is 3 hours.

7. The method for preparing the fractionated lignin high stability anionic dispersed rosin glue according to claim 1, characterized in that: In step 2, the drying temperature is 50° C. and the drying time is 12 h.

8. Use of the method for preparing the fractionated lignin high-stability anionic dispersed rosin glue according to claim 1 in preparing a sizing agent according to any one of claims 1 to 7.